Документальні пам’ятки Харківської обсерваторії: проблеми збереження та введення до наукового обігу - Балишев, М. (Архіви України, 2008)
The article highlights the history of arrangement and systematization related
to the Struves’ family archives – three generations of a well-known astronomer’s
dynasty, kept at Kharkiv observatory. Special emphasis is made on miserable
preservation conditions and critical physical state of the documents which pose a
threat to this unique documentary heritage.